FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ANSIETAS PADA LANSIA TENTANG COVID-19 - Awaeh, Novita; Wetik, Syenshie; Laka, Angela (Lasalle Health Journal, 2022)
Background: COVID-19 that occurs around the world has caused an increase in cases of anxiety, including in the elderly. This increase in incidence is due to the high death rate due to Covid-19 and the circulation of hoax information that dominates media reports including social media. Objective: This study aims to analyze factors related to the incidence of anxiety in the elderly about covid-19. Method: The design of this study is descriptive quantitative, with a cross-sectional approach that uses purposive sampling techniques with a total sample of 51 respondents. The statistical test used is chi-square. Results: The results were that there was a significantrelationship between age factors with the incidence of anxiety (p-value 0.000 < 0.05), gender factors with incidence of anxiety (p-value 0.034 < 0.05), health factors with incidence of anxiety in the elderly (p-value 0.000 < 0.05), social support factors with incidence of anxiety (p-value 0.001 < 0.05) and self-concept factors with incidence of anxiety (p-value 0.001 < 0.05). Conclusion: There is a significant relationship between factors of age, gender, health, social support and self-concept with the incidence of anxiety in the elderly about Covid-19 in Tewaan Village, Ranowulu District, Bitung City.